Benefits of Progressive Muscle Relaxation to Improve Sleep Quality in Youth - Kanthi Suratih; Erindra Budi (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2022)
Sleep disturbances are common among teenagers in the era of the Covid-19 pandemic due to the implementation of online learning. .The results of several systematic reviews and meta-analyses on eight databases to determine the impact of COVID-19 on children and adolescents (aged < 18 years) found anxiety and depression disorders, reactions to emotional and mental health, psychological distress, and behavioral disorders, sleep disturbances, nightmares and it all can affect aspects of adolescent life, especially in orphanages where they do not have relatives and parents. So it is felt that it is very important to do a non-pharmacologic therapeutic action to overcome these problems and progressive muscle relaxation is one of the easy methods to be carried out by teenagers in orphanages. This study aims to determine the effect of progressive muscle relaxation on adolescent sleep quality. using method. pre- and post-test experiments with a control group. Involving research subjects as many as 42 teenagers. Data were analyzed by paired t test not using the SPSS 21 program. There was a significant difference between the control and treatment groups with a mean of 6,52 and 4,20 and getting a p-value of 0.003 so that it can be concluded that the implementation of progressive muscle relaxation can be useful for making good sleep quality for adolescents in orphanages.Keywords: progressive muscle relaxation; sleep quality; teenagersManfaat Relaksasi Otot Progresif Untuk Tingkatkan Kualitas Tidur RemajaABSTRAK Gangguan tidur sering terjadi di kalangan remaja di era pandemi Covid-19 akibat penerapan pembelajaran daring. .Hasil beberapa tinjauan sistematis dan meta-analisis pada delapan database untuk mengetahui dampak COVID-19 pada anak dan remaja (usia <18 tahun) ditemukan gangguan kecemasan dan depresi, reaksi terhadap kesehatan emosional dan mental, tekanan psikologis, dan perilaku gangguan, gangguan tidur, mimpi buruk dan itu semua dapat mempengaruhi aspek kehidupan remaja terutama di panti asuhan dimana mereka tidak memiliki kerabat dan orang tua. Sehingga dirasa sangat penting dilakukan tindakan terapi non farmakologis untuk mengatasi permasalahan tersebut dan relaksasi otot progresif merupakan salah satu metode yang mudah dilakukan oleh remaja di panti asuhan. Penelitian ini bertujuan untuk mengetahui pengaruh relaksasi otot progresif terhadap kualitas tidur remaja. menggunakan metode. eksperimen sebelum dan sesudah tes dengan kelompok kontrol. Melibatkan subyek penelitian sebanyak 42 remaja. Data dianalisis dengan uji t berpasangan tidak menggunakan program SPSS 21. Terdapat perbedaan yang signifikan antara kelompok kontrol dan perlakuan dengan mean 6,52 dan 4,20 serta mendapatkan p-value 0,003 sehingga dapat disimpulkan penerapan relaksasi otot progresif dapat bermanfaat untuk membuat tidur nyenyak. kualitas remaja di panti asuhan. Kata kunci: relaksasi otot progresif; kualitas tidur; remaja